Terengganu Board game (Turtle O'clock) - Abu Bakar, Alia Huda; Othman, Muhammad Fakri (Applied Information Technology And Computer Science, 2021)
Turtle O’clock game application is a Terengganu Travelling board game that is meant to help user to know more about places in Terengganu. The objectives of this project are to design and develop a Terengganu travelling 3D board game that helps to give brief ideas about Terengganu using the Unity game developer and to test the game prototype to the target user which is person who would love to travel. The methodology used to develop this application is Game Development Life cycle (GDLC) methodology which consist of six phases initiation, pre-production, production, testing, beta testing and release, that was chosen for its practicality in developing games application for it has production cycle. Based on the user testing on this game application, the data shows that 100% of user learns new places from the game application. Therefore, it can be concluded that games and 3D approach can help to make user learn and memorize new things better than from common reading materials and this finding can be applied to educational based application for kids.